PENGARUH KONSUMSI DARK CHOCOLATE TERHADAP FUNGSI KONSENTRASI VISUAL MAHASISWA FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS KATOLIK INDONESIA ATMA JAYA - Jeremiah Mai Nugraha; Hanna Yolanda; Linda Suryakusuma (Atma Jaya Catholic University of Indonesia, 2019)
Introduction: Cognitive function is essential for medical students to support learning at the university. One part of cognitive function that is very important in student learning is visual concentration. Visual concentration is the process of maintaining a concentration of thought on a visual object by putting aside other things that are not related. Concentration can be increased in several ways, one of which is to consume nutritious foods that contain flavonoids such as dark chocolate. The purpose of this study was to determine the effect of dark chocolate consumption on visual concentration of cognitive function in Atma Jaya’s medical students.Methods: This was an experimental study and the data were tested using t-paired statistical test. The research was conducted from March to April 2019 at Atma Jaya Catholic University of Indonesia School of Medicine and Health Sciences, Jakarta. The data ovtained from Stroop Test before and after intervention of dark chocolate. A total of 51 respondents were selected according to the research criteria.Results: As many as 48 people (94.1%) experinced an increase in the Stroop Test Score, a person (2%) did not experience a change in the Stroop Test Score, and two people (3.9%) experinced a decrease in the Stroop Test Score. The result of statistical test show significant results (p<0.01). The average score before the intervenion was obtained at 77.02±10.42 and the average score after the intervention was obtained at 77.02±11.81 (Δ= +12.26).Conclusion: There is an effect of dark chocolate consumption on visual concentration of cognitive function in Atma Jaya’s medical student